The Future of Indonesian Fishing Communities Amidst Climate Change - Sani, Tajudeen; Ulya, Siti Alimatul; Razak, Tun Muhammad (Universitas Negeri Semarang, 2024)
This study explores the future of Indonesian fishing communities in the face of climate change, focusing on the intersection of environmental, social, and economic challenges. Indonesia, an archipelagic nation with a significant reliance on marine resources, is particularly vulnerable to the impacts of climate change, including rising sea levels, changing fish migration patterns, and extreme weather events. The study employs a multi-disciplinary approach, combining climate science, fisheries management, and socio-economic analysis, to provide a comprehensive understanding of the challenges and potential solutions for these communities. Key findings highlight the disproportionate effects of climate change on small-scale fishers, who are often the most vulnerable to environmental shifts due to limited adaptive capacity and reliance on declining marine resources. Novel contributions include the identification of community-driven adaptation strategies and the role of traditional ecological knowledge in enhancing resilience. Furthermore, the paper emphasizes the urgent need for policy interventions that integrate both local and global efforts to mitigate the impacts of climate change on Indonesia's fishing sector. This research contributes to the ongoing discourse on sustainable fisheries management by offering practical recommendations for enhancing the adaptive capacity of Indonesian fishing communities, ensuring food security, and preserving marine biodiversity. The findings underscore the necessity for a holistic approach, combining scientific, social, and economic considerations to safeguard the future of these communities amid the growing climate crisis.